EFFECT OF CHITOSAN GELATINIZATION TEMPERATURE ON WATER ABSORPTION AND WATER RETENTION OF CHITOSAN BASED UREA FERTILIZER - Mohamad, Noraiham; Abdul Hamid, Nor Nadiah; ABD RAZAK , JEEFFERIE; Mohd Fairuz, Dimin (2013)
Chitosan is highly potential to be blended together in urea fertilizer for slow release properties due to its unique polymeric cationic character and gel forming properties. In agriculture, the slow release properties are normally indicated by the ability of urea fertilizer to absorb and retain water since nitrogen is released to the environment once urea is in contact with water or enzyme. This paper investigates the effect of chitosan content and gelatinization temperature on physical properties of chitosan based urea fertilizer. The chitosan content was varied from 0, 3, 5, 7 and 10 pph. Chitosan based urea fertilizer was prepared through a direct wet mixing using laboratory set up consist of beaker, magnetic stirrer and hotplate. The properties of chitosan based urea fertilizer were compared at two different mixing temperatures which are 60oC and room temperature of 25 ± 3oC. The mixture was then dried in an oven at 60oC for 8 hours before fabricated into pellet using a hydraulic hand presser. Water absorption and water retention analysis were carried out to measure amount of water intakes and amount of water retain in fertilizer. It was observed that mixing temperature has negligible effect on water retention of the fertilizers. However, mixing at room temperature resulted of higher water absorption values than mixing at 60C. These results were supported by X-Ray Diffraction analysis conducted on the fertilizers.